Monoclonal antibody NIM-R3 substitutes for B-cell growth factor. - Greenwood, M R (1986)
A rat monoclonal antibody (NIM-R3) was found to be reactive with activated mouse B cells but neither activated T cells nor small resting lymphocytes, T or B. The antibody stains antibody-forming cell precursors within 48 hr of primary or secondary immunization in vivo, but not at longer times (greater than 14 days) immunization. When added to cultures of spleen cells responding in vitro to dinitrophenylated bovine, IgG, the number of antibody-forming cells was increased. NIM-R3 also maintained the proliferation of purified B blasts in the absence of lipopolysaccharide, but did not activate small resting B cells in the presence of anti-Ig. NIM-R3 could replace B-cell growth factor (BCGF II) in cultures of the murine B-cell lymphoma BCL1 inducing proliferation but not differentiation. Finally, competition was demonstrated for binding sites on BCL1 cells between BCGF II and NIM-R3, but not between NIM-R3 and T-cell replacing factor (B15-TRF). We suggest that NIM-R3 may represent a novel specificity and may be directed against the cell surface receptor for BCGF II, and in turn this receptor may be independent of the B15-TRF and BSF1 receptors.